Influence of the Sintering Type in Ceramics Blocks for Cad-Cam - Kreidler, Martin A. M.; Oliveira, Osmir B. [UNESP] (Univ Costa Rica, Fac Odontologia, 2016)
The aim of this study was to characterize the influence of the sintering type in the flexural strength and hardness of ceramic blocks for CAD-CAM. Four type of ceramic blocks were selected and distributed according to the type of sintering to be performed: Group G1 - In-Ceram (R) Alumina / liquid state; Group G2 - In-Ceram (R) AL / solid state; Group G3 - In-Ceram (R) Zircon / liquid state; Group G4 - In-Ceram (R) YZ / solid state. All blocks were cut in bar shape with dimensions of 25 x 5 x 2 mm. and submitted to the three-point bending test and to the Vickers hardness test method. The results, after statistical analysis, showed that the average flexural strength of group G1 (351.7 MPa) and group G3 (356.3 MPa) were significantly lower than those of group G2 (421.9 MPa) and group G4 (758.4 MPa); as well as all hardness averages were significantly different, being higher for group G2 (1.936,6 HV) and group G4 (1.321,4 HV), when compared to group G1 (1.173,3 HV) and group G3 (1.094,6 HV). It was concluded that the solid state sintering proved to be more efficient to obtain maximum densification of the ceramics blocks, resulting in high values of flexural strength and hardness.
Keywords: CAD-CAM; Ceramics; Dental porcelain; Dental material; Surface properties; Hardness